Alternative Public Transport Route Planning of Balikpapan–Nusantara New Capital City (IKN) using PTV VISUM - Arief Hidayat; Khairi Ahza Hail Keliwar; Ummu Kultsum Muhammad; Dion Putra Kurniawan (Tinta Emas Publisher, 2026)
The development of Nusantara Capital City (IKN) has increased the importance of regional connectivity between IKN and Balikpapan as one of its supporting cities. However, the development of public transport routes connecting the two areas requires consideration of travel demand, road network characteristics, and connectivity with existing transport services. This study aims to develop and compare alternative public transport routes between Balikpapan and IKN using PTV VISUM. The study employed a quantitative approach based on the Four Step Model, consisting of trip generation, trip distribution, mode choice, and trip assignment. Primary data were collected through a Home Interview Survey involving 400 respondents, while secondary data included road networks, land use, and existing public transport services. Travel demand was represented through an Origin-Destination Matrix and assigned to the modeled network in PTV VISUM using the User Equilibrium method. The analysis produced two alternative routes connecting Batu Ampar Terminal in Balikpapan with the IKN Rest Area. Route 1 covers 88.9 km through the non-toll Samboja–Sepaku corridor, whereas Route 2 covers 80.7 km through the Balikpapan–IKN Toll Road and connects with IKN VVIP Airport. Route 2 provides an 8.2 km shorter corridor, while both alternatives offer different network and service characteristics. These findings provide an initial basis for developing Balikpapan–IKN public transport by integrating travel demand, network characteristics, route length, and connectivity with strategic transport nodes.